فعالية نموذج الهرم المضارع في تعلم اللغة العربية لدى طلاب السنة الثاني في ولاية بوتراجايا: The Effectiveness of the Morphological Pyramid Model in Enhancing Arabic Language Acquisition Among Secondary School Students in Putrajaya - Sharol Rizal, Nur Alia Misha (SIBAWAYH Arabic Language and Education, 2024)
تهدف هذه الدراسة إلى تقييم فعالية نموذج هرم المضارع في تحسين اكتساب مهارات تصريف الفعل المضارع لدى طلاب السنة الثانية الثانوية في مدرسة بيروني بولاية بوتراجايا. تم تحديد مجموعة من الإشكاليات التي يواجهها الطلاب، مثل ضعف القدرة على تصريف الأفعال المضارعة بدقة، وصعوبة اختيار التصريف المناسب بناءً على السياق النحوي. اعتمدت الدراسة على منهج شبه تجريبي باستخدام اختبارات قبلية وبعدية لتقييم أثر النموذج التفاعلي. شملت العينة 30 طالبًا من السنة الثانية، حيث تم تحليل نتائج الاختبارات القبلية والبعدية لقياس التطور في الأداء اللغوي. أظهرت نتائج الدراسة زيادة ملحوظة في متوسط درجات الاختبارات البعدية مقارنة بالقبلية، مما يدل على فعالية استخدام نموذج الهرم المضارع في تحسين استيعاب الطلاب لمهارات تصريف الفعل المضارع. كما توصلت الدراسة إلى أن استراتيجيات التدريس التفاعلية، بما في ذلك دمج التكنولوجيا التعليمية، توفر بيئة تعليمية محفزة تدعم تطوير مهارات الطلاب بشكل أعمق وأكثر استدامة مقارنة بالأساليب التقليدية. بناءً على هذه النتائج، توصي الدراسة بتبني أساليب تعليمية تعتمد على التفاعل والمشاركة الفعالة للطلاب، مع التركيز على استخدام أدوات التكنولوجيا الحديثة كجزء أساسي من عملية التعليم. يعد نموذج هرم المضارع وسيلة فعالة في تحسين الأداء الأكاديمي، حيث يوفر بديلاً مبتكرًا للأساليب التعليمية التقليدية التي غالبًا ما تعاني من قصور في تحقيق التفاعل النشط والفهم العميق.This study aims to evaluate the effectiveness of the Morphological Pyramid Model in improving the acquisition of present verb conjugation skills among second-year secondary school students at Al-Biruni School in the state of Putrajaya. A set of challenges faced by the students was identified, such as a weak ability to accurately conjugate present verbs and difficulty in selecting the appropriate conjugation based on the grammatical context. The study employed a quasi-experimental approach using pre- and post-tests to assess the impact of the interactive model. The sample included 30 second-year students, and the results of the pre- and post-tests were analyzed to measure the development in linguistic performance. The results of the study showed a significant increase in the average post-test scores compared to the pre-test scores, indicating the effectiveness of using the Morphological Pyramid Model in improving students' understanding of present verb conjugation skills. The study also concluded that interactive teaching strategies, including the integration of educational technology, provide a stimulating learning environment that supports deeper and more sustainable skill development compared to traditional methods. Based on these results, the study recommends adopting educational strategies that rely on student interaction and active participation, with a focus on using modern technological tools as an essential part of the educational process. The Morphological Pyramid Model is an effective tool in improving academic performance, offering an innovative alternative to traditional teaching methods, which often struggle to achieve active engagement and deep understanding.Keywords: teaching effectiveness, Morphological Pyramid, grammatical conjugation, educational technology, interactive methods.